STUDI KOMPARASI: EFEKTIFITAS PSIKOEDUKASI TERHADAP ADAPTASI PASIEN FRAKTUR DI RSUD JOMBANG - Zuhrotul Umaroh; Elsye Maria Rosa (Fakultas Ilmu Kesehatan, 2016)
Background: The injury is still a major public health problem throughout the country, where two-thirds occur in developing countries, including Indonesia. In Indonesia, recorded injury cases in 2013 reached 84,277 people (8.2%). The negative impacts caused by the fracture appears, which includes; psychological, social, and spiritual. The Department of Health reported that 15% of patients experiencing psychological stress fractures to depression. Psychoeducation efficient in the treatment process and decrease the symptoms of depression that is a component in the psychological response on the existence of a disability condition. Aim: the research aimed todetermine the effectiveness of psychoeducation to the physical adaptation among fracture patients in public hospital of Jombang Method: this is a quasi-experiment research with pre-test and post-test control group design. There were 16 respondents in control group and another 16 respondents for intervention group which was gathered with consecutive sampling. The data were analyzed with parametric analysis using paired sample t-test dan independent t-test. For testing the data normality distribution, Shapiro-wilk analysis was operated. Result: Paired t test sample stated that there was significant difference in the physical adaptation among fracture patients before and after the intervention of psychoeducation (p value = 0,000 ; CI 95% <alpha = 0,05). In the unpaired t test was obtained p value = 0.000; CI 95% <alpha = 0.05, which indicates a significant difference of fracture patients’ adaptation who has given psychoeducation intervention and who has not. Conclusion: the psychoeducation intervention increasedphysical adaptation among fracture patients. Nurses must continue to develop and apply the procedures for implementing psychoeducation fractures primarily in patients with the aim to improve the adaptability of fracture patients.